Psychosocial health of cochlear implant users compared to that of adults with and without hearing aids: Results of a nationwide cohort study. (19th February 2018) - Bosdriesz, J.R.; Stam, M.; Smits, C.; Kramer, S.E.
Abstract : Objectives: This study aimed to examine the psychosocial health status of adult cochlear implant (CI) users, compared to that of hearing aid (HA) users, hearing‐impaired adults without hearing aids and normally hearing adults. Design: Cross‐sectional observational study, using both self‐reported survey data and a speech‐in‐noise test. Setting: Data as collected within the Netherlands Longitudinal Study on Hearing (NL‐SH) between September 2011 and June 2016 were used. Participants: Data from 1254 Dutch adults (aged 23‐74), selected in a convenience sample design, were included for analyses. Mean outcome measures: Psychosocial health measures included emotional and social loneliness, anxiety, depression, distress and somatisation. Psychosocial health, hearing status, use of hearing technology and covariates were measured by self‐report; hearing ability was assessed through an online digit triplet speech‐in‐noise test. Results: After adjusting for the degree of hearing impairment, HA users (N = 418) and hearing‐impaired adults (N = 247) had significantly worse scores on emotional loneliness than CI users (N = 37). HA users had significantly higher anxiety scores than CI users in some analyses. Non‐significant differences were found between normally hearing (N = 552) and CI users for all psychosocial outcomes. Conclusions: Psychosocial health of CI users is not worse than that of hearing‐impaired adults with or without hearing aids. CI users' level of emotional loneliness is even lower than that of their hearing‐impaired peers using hearing aids. A possible explanation is that CI patients receive more professional and family support, and guidance along their patient journey than adults who are fitted with hearing aids.